Development, Characterisation and Application of Monoclonal Antibodies for the Detection and Quantification of Infectious Salmon Anaemia Virus in Plasma Samples Using Luminex Bead Array Technology. - R Hoare; K D Thompson; T Herath; B Collet; J E Bron; A Adams (PLoS ONE)
Infectious salmon anaemia virus (ISAV) is an orthomyxovirus that has had a significant economic impact on Atlantic salmon farming in Europe, North America and Chile. Monoclonal antibodies (mAbs) were developed against Segment 3 (encoding the viral nucleoprotein, NP) of the virus. Six of the mAbs were shown to be specific to ISAV and recognised all isolates from Scotland, Norway and Canada. They reacted with ISAV in enzyme-linked immunosorbent assay (ELISA), indirect fluorescent antibody technique (IFAT) and western blotting. They were also used to develop a novel detection method based on Luminex (Bio-Plex) bead-based flow cytometric technology for the detection of ISAV in the plasma of Atlantic salmon (Salmo salar L.) smolts experimentally infected with ISAV. Fish were challenged by intraperitoneal (i.p.) injection of virus at 50% Tissue Culture Infective Dose (TCID50) = 2.8 x106 per animal. Virus present in plasma of infected fish, collected at 0, 4, 8, 12, 16, 21 and 28 days post infection using a non-lethal sampling method (n = 12 at each time point), was quantified using the optimised Bio-Plex assay. The results obtained with this assay were compared with absolute quantification of the virus by RT-qPCR using SYBR Green I and TaqMan chemistries. The Bio-Plex assay developed using the NP mAbs appears to be a rapid, sensitive method for detecting and quantifying ISAV in small volumes of fish plasma and has the potential to be multiplexed for the detection of other fish pathogens (e.g. during co-infections). To our knowledge this is the first report of the use of Luminex (Bio-Plex) technology for the detection of a fish pathogen.